Prevalence and genetic characterization of clinically relevant extended-spectrum β-lactamase-producing Enterobacterales in the Gulf Cooperation Council countries - Hamad A. Hadi; Hissa Al-Hail; Leena Elsheikh Aboidris; Mahmood Al-Orphaly; Mazen A. Sid Ahmed; Mazen A. Sid Ahmed; Bincy Gladson Samuel; Hana Adam Mohamed; Ali A. Sultan; Sini Skariah (Frontiers Media S.A., 2023)
IntroductionAmong Gram-negative bacteria (GNB), Enterobacterales (Enterobacterales), such as Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae), are the most clinically relevant pathogens in healthcare settings. Infections secondary to these pathogens are widely common but multidrug resistance (MDR) in Enterobacterales has become a significant challenge with increased morbidity, mortality, and cost of management. The escalating global prevalence of MDR in Enterobacterales has led to limited treatment options, raising an urgent need for novel antimicrobial therapy(s) and detailed studies exploring underlying resistance mechanisms. In Enterobacterales, the prime antimicrobial resistance mechanism against β-lactam antibiotics is mainly the production of β-lactamases, particularly extended-spectrum β-lactamases (ESBLs). Although the Gulf region is witnessing major challenges from infections secondary to MDR GNB, the extent of the problem has not been fully evaluated. Therefore, this review aims to address the prevalence and genetic characterization of ESBL-producing Enterobacterales in the Gulf Cooperation Council (GCC) countries.MethodsPubMed® (National Library of Medicine, Bethesda, MD, USA) search was conducted, which looked for academic articles discussing the epidemiology of MDR Enterobacterales in the GCC countries, published in the last 5 years.Results and conclusionsIn GCC countries there is a high prevalence rate of MDR Enterobacterales, particularly ESBLs. Prevalence rates of ESBL-producing Enterobacterales among the Enterobacterales in general clinical samples in the GCC region is 21.6%-29.3%, with a slightly higher prevalence rate in intensive care unit patients (17.3-31.3%) and in patients with urinary tract infections (25.2%-31.7%). ESBL carriers have also been noted in the general community. ESBL-producing Enterobacterales from the GCC region show high levels of resistance to ampicillin, aztreonam, third-/fourth-generation cephalosporins, fluoroquinolones, and trimethoprim-sulfamethoxazole. Intermediate resistance rates are observed against nitrofurantoin, piperacillin/tazobactam, and gentamicin, with increasing resistance observed against tigecycline. The isolates demonstrate low-level resistance to carbapenems, fosfomycin, colistin, and amikacin. Enterobacterales isolates that are concomitant ESBL producers and are carbapenem resistant have been increasingly reported and demonstrate alarmingly increased antibiotic resistance patterns compared with ESBL Enterobacterales. The most prevalent genes for ESBL resistance in the Enterobacterales isolates in the GCC region are: blaCTX-M (subtype group 1) followed by/co-dominated by blaTEM and blaSHV, whereas the most common carbapenem-resistant genes are blaOXA-48 and blaNDM-1.